The Effect of Communication and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable - Afiah, Mita Husna; Kurniawan, Bayu; Setyorini, Noni (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the effect of communication and career development on employee performance with job satisfaction as an intervening variable at PT. Pos Indonesia Kendal City District Office. This research was conducted using quantitative research, using a questionnaire as a research instrument. The sample consisted of 95 respondents, selected using the saturated sampling method. Research data was analyzed using the Structural Equation Modeling (SEM) statistical method with the Smart PLS 4 application. The research data has met the validity and reliability tests, which shows that the results are in accordance with the model requirements to proceed to hypothesis testing. The findings of this research indicate that: (1) Communication has no influence on job satisfaction at PT. Pos Indonesia Kendal City District Office , (2) Career development has a positive and significant effect on job satisfaction at PT. Pos Indonesia Kendal City District Office , (3) Communication is influential positive and significant to employee performance at PT. Pos Indonesia Kendal City District Office , (4) Career development has a positive and significant effect on employee performance at PT. Pos Indonesia Kendal City District Office , (5) Job satisfaction has a positive effect on employee performance at PT. Pos Indonesia Kendal City District Office , (6) Communication has no influence on employee performance through job satisfaction as an intervening variable at PT. Pos Indonesia Kendal City District Office , (7) Career development has a positive and significant effect on employee performance through job satisfaction as an intervening variable at PT. Pos Indonesia Kendal City District Office .